EFFECT OF SOLARISATION ON SCLEROTIA OF SCLEROTIUM ROLFSll CAUSING COLLAR ROT IN BETELVINE - R. K. S. TIWARI**, A. L. DESHPANDE* AND (Indian Phytopathology, 2002)
Experiments were conducted in pots to study the effed of solarisation (heating soil by covering polythene sheets) during summer on Sclerotium roljsii, the collar rot pathogen of betelvine. Different durations of solar treatments were given to sclerotia of fungus. All the betelvine cuttings planted in solarised pots were found free from collar rot disease (mortality 0.0 per cent). Even then, in case of five days solarisation, all cuttings were found free from collar rot infection.